Canine leptospirosis: an Overview of the City of Pelotas, Brazil (Research, Society and Development, 2020)
Leptospirosis is a disease of worldwide importance, both from a veterinarian and a public health point of view. Serological survey through the microscopic agglutination test (MAT) is the standard to diagnose and assess the disease´s distribution in a population.  Stray dogs are important urban reservoirs of leptospirosis and studies regarding their seroreactivity in Brazil are few and far apart. This work reports the seroreactivity of stray dogs to the most important serogroups in the Leptospira genus causing urban leptospirosis in dogs and humans in Pelotas, Brazil: Icterohaemorrhagiae and Canicola. All the animals used in this study were female stray dogs, no distinction regarding age or race was made. Blood samples were collected from 221 animals. The MAT was carried out according to the recommendations of the World Health Organization (WHO). Of the 221 tested animals, 64 were positive for agglutinating antibodies, representing a prevalence of 29%. These results are in accordance with those reported for housed dogs in Pelotas in previous studies. This study represents an important epidemiological update for the leptospirosis scenario in southern Brazil. Furthermore, these reports will aid healthcare agents in controlling both canine and human leptospirosis in the region.